Insights into the bacterial community compositions of peanut worm (Sipunculus nudus) and their association with the surrounding environment - Zhong, Ruzhuo; Huang, Jianqiang; Liao, Yongshan; Yang, Chuangye; Wang, Qingheng; Deng, Yuewen (Frontiers in Marine Science, 2022)
This study characterized the diversity, composition, and interrelationships of bacterial communities in the intestine, coelomic fluid, and culture environment of peanut worm (Sipunculus nudus) through high-throughput sequencing using the Illumina HiSeq sequencing platform. Alpha diversity analysis showed that the highest bacterial community richness and diversity were found in the sediments. Species annotation revealed that Proteobacteria dominated in all samples (48.92%–58.36%), and the other dominant phyla were highly variable, indicating a certain independence between the environment and the composition of the bacterial community of S. nudus. The coelomic fluid of S. nudus contained high concentrations of Bacillus and could be a source of potential probiotic bacteria for isolation and culture. Cluster and operational taxonomic unit Venn diagram analyses showed that the bacterial community composition in the intestine was more similar to that in the sediments compared with water. The predicted functional analysis of bacterial communities indicated that the functions of bacterial communities in the different surrounding environment were highly similar and involved in various aspects, such as membrane transport, amino acid metabolism, carbohydrate metabolism, and replication and repair. Our findings have important implications on the establishment of sustainable microecological regulation and management strategies for S. nudus culture and provide a reference for the development and utilization of probiotic bacteria.